Effects of cocktail of four local Malaysian medicinal plants (Phyllanthus spp.) against dengue virus 2 - Lee, S.H.; Tang, Y.Q.; Rathkrishnan, A.; Wang, S.M.; Ong, K.C.; Manikam, R.; Payne, B.J.; Jaganath, I.B.; Sekaran, S.D. (BioMed Central, 2013)
Background: The absence of commercialized vaccines and antiviral agents against dengue has made the disease a major health concern around the world. With the current dengue virus transmission rate and incidences, the development of antiviral drugs is of vital need. The aim of this project was to evaluate the possibility of developing a local medicinal plant, Phyllanthus as an anti-dengue agent. Methods: Cocktail (aqueous and methanolic) extracts were prepared from four species of Phyllanthus (P. amarus, P. niruri, P. urinaria, and P. watsonii) and their polyphenolic compounds were identified via HPLC and LC-MS/MS analysis. MTS assay was then carried out to determine the maximal non-toxic dose (MNTD) of the extracts, followed by screening of the in vitro antiviral activity of aqueous cocktail extracts against DENV2 by means of time-of -addition (pre-, simultaneous and post-) using RT-qPCR. The differentially expressed proteins in the treated and infected cells were analysed with two dimensional gel electrophoresis experiments. Results: Several active compounds including gallic acid, geraniin, syringin, and corilagen have been identified. The MNTD of both aqueous and methanolic extracts on Vero cells were 250.0 mu g/ml and 15.63 mu g/ml respectively. Phyllanthus showed strongest inhibitory activity against DENV2 with more than 90 of virus reduction in simultaneous treatment. Two-dimensional analysis revealed significantly altered levels of thirteen proteins, which were successfully identified by tandem MS (MS/MS). These altered proteins were involved in several biological processes, including viral entry, viral transcription and translation regulations, cytoskeletal assembly, and cellular metabolisms. Conclusions: Phyllanthus could be potentially developed as an anti-DENV agent.